Branch bark of holm oak (Quercus ilex L.) for reconstructing the temporal variations of atmospheric deposition of hexavalent chromium. (March 2017) - Drava, Giuliana; Anselmo, Marco; Brignole, Daniele; Giordani, Paolo; Minganti, Vincenzo
Abstract: The bark from the annual segments of the branches of holm oak ( Quercus ilex L.) is exposed to trace element deposition for a known period of time and thus it is a possible candidate as a bioindicator for reconstructing historical changes in pollution. A series of samples were analysed for Cr(VI) concentration by electrothermal atomic absorption spectrometry (ET-AAS) after selective extraction in a sodium carbonate solution. In this way the atmospheric deposition of Cr(VI) was reconstructed from 2001 to 2010 in an area where an industrial plant produced Cr(VI) compounds until 2003. The present study shows the potential of this type of sample as a natural archive for persistent pollutants, useful for monitoring changes that occur before a monitoring programme is established, with the advantage of being easy to collect almost everywhere. Graphical abstract: Highlights: Tree bark is a natural archive for persistent pollutants. Cr(VI) levels were measured in the bark of annual segments of branches. Branch bark allowed reconstruction of the temporal variations of atmospheric Cr(VI).